Perlindungan Konsumen Terhadap Perdagangan Rokok Elektrik Kepada Anak Dibawah Umur Di Wilayah Kecamatan Sail Kota Pekanbaru - Farhan, Muhammad Thifal; Ismi, Hayatul; Hendra, Rahmad (Jurnal Ilmiah Wahana Pendidikan, 2025)
National development aims to improve the quality of life for Indonesian citizens in accordance with the principles of Pancasila and the 1945 Constitution. However, violations of consumer protection regarding tobacco products, including electronic cigarettes, remain prevalent. Despite Government Regulation Number 109 of 2012 prohibiting the sale of tobacco products to individuals under 18 years old, weak enforcement and compliance by business actors allow children easy access to electronic cigarettes. This study examines consumer protection in the trade of electronic cigarettes in Sail District, Pekanbaru City. The research method used is qualitative descriptive, with data collected through observations, interviews, and literature studies. The results indicate that the sale of electronic cigarettes in Sail District remains unrestricted, including to minors, due to weak government supervision and non-compliance by business actors. This condition violates Law Number 8 of 1999 on Consumer Protection and Government Regulation Number 109 of 2012. Concrete efforts are needed from the government, society, and Consumer Protection Organizations to strengthen supervision and enforce regulations. Furthermore, public education on the dangers of electronic cigarettes must be enhanced to protect consumers and control their circulation.